Investigating The Academic Literacies Challenges Of International Graduate Students In Master Programmes In An Institution Of Higher Education In Malaysia - Singh, Manjet Kaur Mehar (2013)
This mixed methods research presents the findings of the academic literacies experiences of international graduate students in coursework or mixed mode Master programmes at an institution of higher education in Malaysia. This research investigated the academic literacies demands faced by the international graduate students, the academic literacies challenges experienced by them and the steps employed to overcome the academic literacies challenges to achieve academic success. The conceptual framework of this research comprises the Academic Literacies Model (Lea & Street, 2000), Discipline Enculturation into Community of Practice (CoP) (Lave & Wenger, 1991) and Adult Learning Theory (Knowles, 1984). Academic Literacies Questionnaire created based on selected items from Chang’s (2006) and Evans & Green’s (2007) questionnaire was used to collect the quantitative data from 131 respondents. Qualitative data collection involved focus group interviews with 70 respondents, email correspondence, one-to-one interview with 16 lecturers and course objectives, course requirements and course evaluation documents’ analysis. Quantitative data was analysed using the Statistical Package for the Social Sciences. The focus group interviews and one-to-one interviews’ data were transcribed. The transcribed data and email correspondence data was analysed using the NVivo 10 software.